Minimally Invasive Transpedicular Screw Fixation: Review of 152 Cases in a Single Institution. Steep or Shallow Learning Curve? - Gabrovsky, Nikolay; Ilkov, Petar; Laleva, Maria; Iliev, Cvetoslav; Gabrovsky, Stefan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background In this study, we analyze our institutional experience and personal impressions using minimally invasive spine surgery (MISS) to describe our learning curve and how experience influenced different parameters of the surgical procedure.Methods The study was conducted prospectively and included the first consecutive 152 patients treated with MISS techniques. Patient demographics, surgical data, length of hospital stay, and clinical outcome were reviewed. The cohort was divided into consecutive quarters. Comparison between the quarters and timeline analysis were made to assess the learning curve.Results Only percutaneous transpedicular screw fixation was performed in 65 cases, minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) in 70 cases, and vertebral body replacement in 4 cases. The average blood loss was 113.3, 115, 106.6, and 107.1 mL for each quarter. The average operative time was 155.0, 143.2, 134.5, and 133.8 minutes for the four quarters, whereas the average radiation exposure time was 105.4, 85.3, 46.2, and 45.2 seconds. Differences in the operative time and radiation exposure time between the first to third and the first to fourth quarters were statistically significant.Conclusions Some advantages of MISS techniques could be observed with the very first cases and were not related significantly with the surgeon's experience with MISS. With the acquisition of more experience, some disadvantages of MISS techniques such as longer operative time and longer X-ray exposure can be substantially reduced. Surgical experience, familiarity of the team with the MISS instrumentation, and good patient selection are crucial for achieving all the benefits of MISS.
Keywords: minimally invasive technique; spine surgery; pedicle screw; radiation exposure; learning curve